Share on vk Share on google_plusone_share Share on twitter Share on email More Sharing Services Synthesis, acid-base, and complexing properties of ethylenediaminetetra(O-alkyl)methylenephosphonic acids – the closest organophosphorus analogs of ethylenediaminetetraacetic acid - A.R. Garifzyanov; I.D. Shurygin; I.I. Mirzayanov; F.V. Devyatov (Учёные записки Казанского университета: Серия Естественные науки, 2022)
A number of new complexones – ethylenediaminetetra(O-alkyl)methylenephosphonic acids, the structurally related organophosphorus analogs of ethylenediaminetetraacetic acid – were synthesized. The acid-base and complexing properties of the obtained substances with alkaline-earth and transition metal ions were studied by the methods of potentiometric titration and mathematical simulation. The following parameters were calculated: the ionization constants of the ligands, the stability and deprotonation constants of their 1:1 complexes with metal ions, and the distribution of the complex forms. The calculated stability constants for H4L-Alk ligands and d-elements follow the Irving–Williams series.